2015
DOI: 10.18805/ajdfr.v34i4.6886
|View full text |Cite
|
Sign up to set email alerts
|

Studies on effect of drying temperature and storage time on vitamin-C retention capacity and moisture content of papaya-apple fruit leather

Abstract: In the present investigation a study was conducted to prepare fruit leathers from two different fruit pulps i.e. papaya and apple in various proportions. Further study was carried out in order to evaluate the vitamin C retention of prepared leathers at different temperatures such as 55 0 C, 65 0 C and 75 0 C. All fruit leathers were then analyzed for their organoleptic characteristics such as color, flavor, taste, appearance and overall acceptability during storage period. A study was also carried out to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
6
0
3
Order By: Relevance
“…Results noted for the acidity percentage clearly indicated that the acidity of mixed fruit bar increased with the increasing storage period continuously up to 100 days of storage. A slight increase in acidity during storage was also reported by Fulchand et al (2015) [9] in papaya and apple fruit leather and Shakir et al…”
Section: Acidity Percentagesupporting
confidence: 78%
See 1 more Smart Citation
“…Results noted for the acidity percentage clearly indicated that the acidity of mixed fruit bar increased with the increasing storage period continuously up to 100 days of storage. A slight increase in acidity during storage was also reported by Fulchand et al (2015) [9] in papaya and apple fruit leather and Shakir et al…”
Section: Acidity Percentagesupporting
confidence: 78%
“…Similar results were reported by Khan et al (2014) [17] in guava bar and Litaf et al (2014) [17] in apple leather. Fulchand et al, (2015) [9] concluded similar trend with fall of moisture content in papaya and apple fruit leather.…”
Section: Moisture Percentagementioning
confidence: 76%
“…Papaya ve elma karışımından, üç farklı sıcaklıkta (55, 65 ve 75°C'ler) kurutma ile elde edilen pestillerdeki C vitamini korunumu üzerine yapılan bir çalışmada ise, meyve püresindeki C vitamini miktarı 31,23 mg/100 g iken, 55°C'de kurutulan pestilde 23.42 mg/100 g, 65°C'de kurutulanda 21.86 mg/100 g ve 75°C'de kurutulanda 17.18 mg/100 g olarak bulunmuştur. Kurutma sıcaklığı yükseldikçe kurutma süresi kısalmış ve bu çalışmada bu durum C vitamini korunumunu arttırmıştır [58]. Çilek pestili üzerine yapılan bir başka çalışmada ise yine üç farklı sıcaklıkta (55, 65 ve 75°C'ler) kurutma ile elde edilen pestillerdeki fenolik bileşik miktarlarının yükselen kurutma sıcaklığı ile belirgin şekilde azaldığı (55°C > 65°C > 75°C), bu çalışmada düşük sıcaklık ve uzun kurutma süresinin fenolik bileşik korunumunu daha iyi sağladığı ve 10 haftalık depolama boyunca fenolik bileşik miktarlarının stabil kaldığı bulunmuştur [59].…”
Section: Pesti̇l üReti̇mi̇unclassified
“…1 and In the present study, after preparation of pomegranate leather they were packed into different types of packaging treatments for storage. Similar types of studies where variable packaging material were used for packaging of fruit leather were conducted by Fulchand et al, (2015) and Kumar & Sukhla, (2018). After packaging, storage was done at refrigerated and ambient conditions and analysis was carried upon at different storage intervals.…”
Section: Resultsmentioning
confidence: 86%